Avaliação do envelhecimento do poli (fluoreto de vinilideno) (PVDF) visando aplicações em estruturas para contato com etanol combustível - Silva, Agmar José de Jesus (2017)
This work evaluated the aging of the poly(vinylidene fluoride) (PVDF) exposed to ethanol fuel at temperature of 60°C during times of 30−180 days. The material was also thermally aged to evaluate the temperature-induced effectsin the process. The overall methodology included the physical-chemical/structural characterization, a thermal /thermomechanical study and a mechanical evaluation of the material. Although the aging in ethanol or annealing does not change the structure of the polymer, an increase in the degree of crystallinity was observed and attributed to a thermal effect. Kinetic studies conducted by thermogravimetric analysis (TG) revealed that the ethanol absorbed by PVDF affected its degradation kinetics, reducing the activation energy (Ea) of the main thermal degradation process. Consequently, there was a reduction in the material lifetime. The PVDF suffered significant changes in its dynamic mechanical thermal properties (DMTA), mainly in the T'g region, where the ethanol acted reducing the dynamic storage modulus (E') by plasticizer effect. The ethanol molecules bounded to PVDF also reduced the long-chain mobility due to steric effect, increasing the activation energy for promoting the Tg. E' master curves show that there was a loss of long-term durability when the PVDF was subjected to heated ethanol. The instrumented microindentation (micro-TII) tests show that the instrumented elastic modulus (EIT) increased with increasing of the loading rate and decreased with increasing of the maximum load. After aging in ethanol, the EIT and the microindentation (HIT) were reduced, indicating a non-negligible degradative effect of the fluid on the surface of the material.